Electric dipole polarizability constraints on neutron skin and symmetry energy - von Neumann-Cosel, Peter; Tamii, Atsushi (Frontiers in Physics, 2025)
We review the experimental knowledge on the dipole polarizability (DP) of nuclei and its relation to the neutron skin thickness and properties of the neutron-rich matter equation of state (EOS). The discussion focuses on recent experiments using relativistic Coulomb excitation in inelastic proton scattering at extreme forward angles covering a mass range from 40Ca to 208Pb. Constraints on the neutron skins and the density dependence of the symmetry energy are derived from a systematic comparison to calculations based on density functional theory (DFT) and ab initio methods utilizing interactions derived from chiral effective field theory (χEFT). The results consistently favor a soft EOS around or slightly below the saturation point. An outlook is provided on possible improvements in the precision achievable in stable nuclei and studies of exotic neutron-rich unstable nuclei with upcoming experimental facilities.